Dual electrospinning with sacrificial fibers for engineered porosity and enhancement of tissue ingrowth. Issue 6 (29th April 2016) - Voorneveld, Jason; Oosthuysen, Anel; Franz, Thomas; Zilla, Peter; Bezuidenhout, Deon
Abstract: Porosity, pore size and pore interconnectivity are critical factors for cellular infiltration into electrospun scaffolds. This study utilized dual electrospinning with sacrificial fiber extraction to produce scaffolds with engineered porosity and mechanical properties. Subsequently, scaffolds were covalently grafted with heparin, a known anti‐coagulant with growth‐factor binding properties. We hypothesized that the tissue ingrowth would correlate positively with the porosity of the scaffolds. Pellethane® (PU) was spun simultaneously with poly(ethylene oxide) (PEO, subsequently extracted). Low, medium and high porosity scaffolds and heparinized versions of each were characterized and implanted in vivo for evaluation of cellular infiltration and inflammation subcutaneously in male Wistar rats (7, 14 and 28 days, n  = 6). Average pore‐size for low (76 ± 0.2%), medium (83 ± 0.5%) and high (90 ± 1.0%) porosity scaffolds was 4.0 ± 2.3 µm, 9.9 ± 4.2 µm and 11.1 ± 5.5 µm ( p  < 0.0001). Heparinization resulted in increased fiber diameter (3.6 ± 1.1 µm vs. 1.8 ± 0.8 µm, p  < 0.0001) but influenced neither pore‐size ( p  = 0.67) nor porosity ( p  = 0.27). Cellular infiltration for low, medium and high porosity scaffolds reached 33 ± 7%, 77 ± 20% and 98 ± 1% of scaffold width, respectively, by day 28 of implantation ( p  < 0001); heparinization did not affect infiltration ( p  = 0.89). The ultimate tensile strength (UTS) and Young's modulus ( E y ) of the constructs increased linearly with increasing PU fiber fraction (UTS: r 2  = 0.97, p  < 0.0001, E y : r 2 = 0.76, p  < 0.0001) and heparinization resulted in decreased strength but increased stiffness compared to non‐heparinized scaffolds. Increased PEO to PU fraction in the scaffold resulted in predictable losses to mechanical strength and improvements to cellular infiltration, which could make PEO to PU fraction a useful optimization parameter for small diameter vascular grafts. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 105B: 1559–1572, 2017.